Effect Of Kenikir Leaves (Cosmos caudatus Kunth.) on Erythrocyte and Hematocrit Changes in Male Secondhand Smoking Wistar Rats - Nur’aini Synthia Maharani; Fitri Komala Sari; Amilia Yuni Damayanti (Universitas Veteran Bangun Nusantara, 2021)
BACKGROUND: Cigarette smoke harmful for body, including secondhand smoker. Chemical contain in cigarette smoke can increase free radicals, and decreasing the level of erythrocytes and hematocrit. Kenikir usually eaten raw as lalap. Flavonoid in kenikir has many health benefit such as anti-inflammatory activity and improving blood circulation. OBJECTIVES: This study aims to determine the effect of kenikirleaves on erythrocytes and hematocrit of the blood of secondhand smoker’s rat. METHODS: the samples were divided into 3 groups (the control group and the treatment group 1 and 2). Each group consists of 10 male Wistar rats, the control group was only given the exposure of cigarette smoke, while the treatment group 1 and 2 were given the exposure to cigarette smoke by giving kenikir leaves at a dose of 4.5 grams and 6.3 grams. Blood sampling was carried out on days 0, 7 and 14 through the retro-orbitalis sinus using the Hematocrit capillary, collected into the microtube then measuring the blood sample parameters using the Hematology Analyzer Sysmex KX-21®. Data were analyzed with One Way Anova test, and posthoc the DMRT. RESULTS: there was a significant effect between the control group against the treatment group 1 and 2 (p<0.05). there were no significant differences between kenikir leaves groups with a dose of 4.5 grams and 6.3 in increasing red blood cell profile (p<1.00). CONCLUSION: there was significant effect of kenikir leaf on erythrocytes and hematocrit profile at a dose of 4.5 gram and 6.3 gram. Keywords: Cigarette Smoke; Erythrocytes; Hematocrit; Kenikir Leaves; Secondhand Smoker